Спектрофотометричне вивчення взаємодії β-циклодекстрину та бензену у водних розчинах - Trofymchuk, I. M.; Lyashenko, D. Yu.; Belyakova, L. A. (Chuiko Institute of Surface Chemistry National Academy of Sciences of Ukraine, 2009)
The interaction of molecules of benzene and β-cyclodextrin in aqueous solutions has been studied by means of UV spectroscopy. Given the change of absorption parameters of UV spectra of aqueous solutions of benzene after adding β-cyclodextrin a stoichiometric composition and formation parameters of supramolecular structures “β-cyclodextrin –benzene” were established. It was proved, that in aqueous solutions essentially 1:1 inclusion complex [β-CD] : [Benz] is formed. Stability constant for 1:1 inclusion complex at 18 – 30 °С, and thermodynamic parameters of its formation were calculated.